News sentiment in the gold futures market - Smales, Lee A. (Journal of Banking & Finance, 2014)
This article utilises commodity specific news sentiment data provided by Thomson Reuters News Analytics to examine the relationship between news sentiment and returns in the gold futures market over the period 2003–2012. There is an asymmetric response to news releases with negative news sentiment invoking a greater contemporaneous response in returns of gold futures. There is evidence to support the supposition that net trader positions significantly impact the identified sentiment relationship with the effect greatest when traders are holding positions contrary to their natural position; this may be explained by constraints imposed on traders in terms of credit availability, exchange imposed limits, or inventory required for physical settlement. Recession, and associated changes in credit costs, impact the size of net positions and the news sentiment/return relationship.